198k views
2 votes
I dont know how to do this so yeah

I dont know how to do this so yeah-example-1

1 Answer

4 votes

Answer:

a). x = 12

b). m∠H = 90°

m∠I = 58°

m∠J = 62°

Explanation:

a). Use the property of a triangle,

" Sum of all the angles in a triangle is 180°"

(2x + 34)° + (4x + 14)° = 180°

(2x + 4x) + (34 + 14) = 180

6x + 48 = 180

6x = 180 - 48

6x = 132

x =
(132)/(6)

x = 12

b). m∠H = 90° [Given]

m∠I = (2x + 34)° = [(2 × 12) + 34]°

m∠I = 58°

m∠J = (4x + 14)° = [(4 × 12) + 14]°

m∠J = 62°

User DrKaoliN
by
4.6k points